The overall image of Slovenia among Croatian students of business and economics - Ozretić Došen, Đurđana (Naše gospodarstvo, 2008)
The objective of the paper is to analyze the overall image of Slovenia among Croatian students of business and economics. A very short, relevant literaturere view on the country image construct is presented in the first part of the paper. The second part describes the methodology and results of the primary research. The research has shown that Croatian students of business and economics have homogeneous assessments of the Slovenian image dimensions of average and less importance for the overall country image profile. However, their assessments of four out of six image dimensions of the greatest importance are not homogeneous and depend on the level of experience they have with Slovenia. Students who are more informed about Slovenia have a more positive and a more complete picture.
Keywords: mnenjske raziskave; Croats; Hrvati; student; študenti; javno mnenje; Slovenia; Slovenija; state; država